2017
DOI: 10.1038/ng.3773
|View full text |Cite|
|
Sign up to set email alerts
|

Acquired CYP19A1 amplification is an early specific mechanism of aromatase inhibitor resistance in ERα metastatic breast cancer

Abstract: Tumor evolution is shaped by many variables, potentially involving external selective pressures induced by therapies1. After surgery, estrogen receptor (ERα) positive breast cancer (BCa) patients are treated with adjuvant endocrine therapy2 including selective estrogen receptor modulators (SERMs) and/or aromatase inhibitors (AIs)3. However, over 20% of patients relapse within 10 years and eventually progress to incurable metastatic disease4. Here we demonstrate that the choice of therapy has a fundamental infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
87
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(90 citation statements)
references
References 39 publications
2
87
0
1
Order By: Relevance
“…In order to study the dynamic process of ET resistance, we exploited an in vitro system that maximises reproducibility while minimising confounding factors 15,27 . Long-term oestrogen deprived (LTED) cells originate from ESR1 wild-type MCF7 that have been deprived from oestradiol for one year.…”
Section: Phenotypical Equivalent Of Fully Resistant Clones Is Absentmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to study the dynamic process of ET resistance, we exploited an in vitro system that maximises reproducibility while minimising confounding factors 15,27 . Long-term oestrogen deprived (LTED) cells originate from ESR1 wild-type MCF7 that have been deprived from oestradiol for one year.…”
Section: Phenotypical Equivalent Of Fully Resistant Clones Is Absentmentioning
confidence: 99%
“…However, this same model is mostly inconsistent with the decade-long latency observed in luminal BCa. In addition, despite recent studies showed that the majority of the genetic lesions in BCa are accumulated during the early phases of tumour development 5,13 , they failed to identify any major driver associated to metastasis and resistance, with the exception of a minor fraction of cases showing either ESR1 mutations or CYP19A1 amplification [14][15][16][17] . Yet, the transcriptomes of the resistant cells are profoundly heterogeneous and different from those of the primary tumour [18][19][20] , suggesting a contribution of non-genetic mechanisms 21 .…”
Section: Introductionmentioning
confidence: 97%
“…Especially for metastases, their genetic landscape may be fundamentally altered by choice of therapy. For example, 21.5% of metastatic breast cancer patients acquired CYP19A1 gene (encoding aromatase) amplification after aromatase inhibitor (AI) treatment, while such mutations only accounted for a minor fraction of those found in patients who had undergone another therapy (Magnani et al, 2017). …”
Section: Genetics and Genomics Of Metastatic Tumor Cellsmentioning
confidence: 99%
“…nuclear factor kappa-light-chain-enhancer of activated B cells, NF-kB) to drive metabolic rewiring and resistance mechanisms [3][4][5] . In hormone-dependent tumours, such as those of the mammary gland, the therapeutic failure of endocrine therapy (ET) is linked with alterations in the cholesterol metabolism 6,7 . Cholesterol and cholesterol-derived intermediates are recognised determinants in the oncogenic reprogramming of hormone responsive cancer cells 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Cholesterol and cholesterol-derived intermediates are recognised determinants in the oncogenic reprogramming of hormone responsive cancer cells 6 . Metastatic, ET-resistant breast cancer cells show increased expression of CYP19A1, a member of the cytochrome C p450 monooxygenase enzymes 7 , which catalyses the last steps of oestrogen synthesis from cholesterol. This prompted the question whether mitochondrial pathways associated with lipid transport are important players of this adaptive response, and whether a physical interaction is established to expedite this route of cellular communication.…”
Section: Introductionmentioning
confidence: 99%